Comparative study of the efficacy of olmesartan/amlodipine vs. perindopril/amlodipine in peripheral blood pressure after missed dose in type 2 diabetes. Issue 2 (February 2016) - Redon, Josep; Pichler, Gernot
Abstract : Introduction: Combination therapy is needed to control blood pressure (BP) in a large number of hypertensive patients with diabetes mellitus. Adherence to treatment is a major clinical problem; therefore, the time duration of the antihypertensive action of a drug determines BP control when a dose is skipped. Objectives: The aim was to determine whether the fixed-dose combination of olmesartan/amlodipine provides equal efficacy and safety as the perindopril/amlodipine combination when a drug dose is missed. Methods: In this noninferiority trial with a randomized, double-blind, double-dummy parallel group, controlled design, 260 patients received either olmesartan 20–40 mg/amlodipine 5–10 mg or perindopril 4–8 mg/amlodipine 5–10 mg for 24 weeks. The main outcome was the sitting office DBP after 24 weeks of treatment at 48 h from last administration. Results: The olmesartan/amlodipine combination reached noninferiority criteria in reduction of office DBP after 24 weeks of treatment and after the missed dose, compared with the perindopril/amlodipine combination (−11.7 and −10.5 mmHg, respectively). Office SBP and pulse pressure were significantly lower in both groups after 24 weeks of treatment and 48 h after the missed dose, observing a trend to greater SBP reduction in the olmesartan/amlodipine group. Conclusions: The combination olmesartan/amlodipine is safe, well tolerated, and as effective as the combination of perindopril/amlodipine in the control of essential hypertension in patients with diabetes mellitus. A missed dose does not leave the patients unprotected in both treatments; however, a faster control with less dose increment is observed with olmesartan/amlodipine. Abstract : Supplemental Digital Content is available in the text